ANALISIS KETIDAKSANTUNAN BERBAHASA PADA BERITA ONLINE TENTANG ANCAMAN PENYEBARAN OMICRON PANDEMI COVID-19 TAHAP 3 - Reni Sagita Br Barus; Yusni Khairul Amri (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
This study aims to determine language impoliteness in online news, especially in online news about the spread of Omicron "Covid-19 pandemic phase 3". The object of formal research is the use of words that use Geoffrey Leech's Theory as a reference, and the object material in the form of maxims that are carried out, maxims of generosity, maxims of appreciation, maxims of simplicity, maxims of appreciation, maxims of consensus, and maxims of sympathy. The object of research material in the background of language speech problems that have an implicit meaning as communication used in conversation by reporters and resource persons during the interview process. This study aims to determine the analysis of language impoliteness through pragmatic studies. The method used is descriptive research in qualitative form and uses a note-taking technique. This research instrument was carried out by means of a documentation study by observing the language used in the online news of covid-19. The results of the data analysis of this study indicate that there is a lot of language use that is not suitable for use in online beita. By combining the six maxims, the data obtained are 81 utterances and 14 utterances that violate language politeness, including 3 maxims of generosity, 2 maxims of generosity, 2 maxims of praise, 3 maxims of humility, 3 maxims of consensus, 1 maxim of sympathy.